Pathologizing Suffering and the Pursuit of a Peaceful Death - Rich, Ben A. (Cambridge quarterly of healthcare ethics, 2014)
The specialty of psychiatry has a long-standing, virtually monolithic view that a desire to die, even a desire for a hastened death among the terminally ill, is a manifestation of mental illness. Recently, psychiatry has made significant inroads into hospice and palliative care, and in doing so brings with it the conviction that dying patients who seek to end their suffering by asserting control over the time and manner of their inevitable death should be provided with psychotherapeutic measures rather than having their expressed wishes respected as though their desire for an earlier death were the rational choice of someone with decisional capacity. This article reviews and critiques this approach from the perspective of recent clinical data indicating that patients who secure and utilize a lethal prescription are generally exercising an autonomous choice unencumbered by clinical depression or other forms of incapacitating mental illness.